Instructional tips from God in Surat Joseph (Yusif) and its benefit in the Educational Process - Taha, Maysoon; Khalaf, Abdullah (Islamic Sciences Journal, 2023)
The educational aspect of the Holy Qur’an is of special significance if it is not the basic factor. There is no verse that does not have an educational imprint while dealing with a specific issue, and the issues that the verses of the Holy Qur’an, in its two parts, Meccan and Madani, were exposed to, dealt explicitly or not with educational dimensions, through the multiplicity of its methods and Its means, for example, through the story, or encouragement and intimidation, proverbs or dialogue, the Qur’anic education comes to achieve its purposes in calling for many values and ideals aimed at building a virtuous society in which virtuous values and morals prevail and justice and equality prevail, and to such meaning many researchers has go on.